Spathodea Campanulata: Een antidiabetisch geneesmiddel? - Laekeman, Gert; Niyonzima, Gaspard; Scharpe, Simon; Vlietinck, Arnold; Mets, Tony (Afrika Focus, 1992)
Decoctions of the stem back of Spathodea campanulata (SC) are currently used in Rwanda to treat insulin- and non insulin-dependent diabetics. In order to confirm and further examine hypoglycemic activity of this plant we set up a research project with as final objective a possible standardisation of Spathodea in antidiabetic therapy in Rwanda. Up to now we were able to confirm the blood sugar lowering effect of SC in hyperglycemic mice (Iiyperglycemia provoked by streptozotocin = SZ). Also hyperglycemia in glucose loaded mice (glucose tolerance test = GTT) could be tempered by SC. Despite these clearcut hypoglycemic activity, no rise of insulin was seen in the SC treated mice. Tlie activity must be due to some other mechanism of action. Tlie search for active principles did not lead to satisfying results up to now. We have only indirect evidence for the presence of sugar-like compounds, as SC decoctions enhance the glycemia transiently. Some hypotheses are formulated with regard to mechanisms of action and active compounds of SC. These aspects will guide future research.